Projeto UNESCO: quatro respostas para a questão racial no Brasil - Praxedes, Rosângela Rosa (2012)
In a post-Second World War background, UNESCO (United Nations Educational, scientific and Cultural Organization) sponsors a program of studies on race relations in Brazil well known as "UNESCO Project". This doctoral thesis bases on theoretical approaches about race relations in Brazilian society since the Decade of 1930. It conducts an analytical and interpretive study, historically grounded in four surveys developed nationally within UNESCO Project in the early 1950s. In the first chapter, we discussed concepts that pointed Brazil as a racial paradise and accredited it to become "a great laboratory" to study race relations. The second chapter provides a discussion on the possibilities of social mobility for Black people in Brazil according to a study developed by René Ribeiro in Pernambuco: Religião e relações raciais (Religion and racial relations). The third chapter brings up a discussion about the research made by L.A. Costa Pinto - O negro no Rio de Janeiro relações de raça numa sociedade em mudança (The Black in Rio de Janeiro race relations in a changing society). In the following chapter, we discussed the study Relações raciais entre negros e brancos em São Paulo (Racial relations between black and white men in São Paulo), created by Roger Bastide and Florestan Fernandes. Then we closed the fifth chapter with a research developed by Thales de Azevedo in Bahia, As elites de cor um estudo de ascensão social (The elites of color a study on upward social mobility). In our final considerations, we systematize the aspects that characterize each study used along the thesis in order to understand how the researchers - who engaged in UNESCO project - faced the opportunities and obstacles to upward social mobility of black people in Brazil. This thesis aims to disclose empirical and theoretical concepts developed on researches at UNESCO Project, so that we can help recollecting its theoretical, empirical and political relevance. In addition, we intend to further studies on race relations, class and social mobility in Brazil, as well as contribute somehow to critic academic production on race relations in this society